2017
DOI: 10.1007/s11695-017-2610-0
|View full text |Cite
|
Sign up to set email alerts
|

Banding the Sleeve Improves Weight Loss in Midterm Follow-up

Abstract: BLSG is a safe procedure showing similar comorbidity to conventional LSG. However, BLSG leads to a higher rate of postoperative regurgitation. Weight loss is significantly improved 3 years after surgery. Hence, additional ring implantation might be an option for increased restriction in LSG surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Furthermore, none of the patients who underwent BSG in the report by Lemmens et al had %EBWL < 50% at 4 years. Also, Fink et al reported %EBWL of 66.74% and %TBWL of 38.2% after BSG, which were significantly greater than those in the SG patients in their study. Lemmens et al explained in the study that the main effect of the ring or band in SG is satiety more than the physical restriction and slowing of the movement of food, and this mechanism causes continued restriction and triggers the ileal brake mechanism because of the fast transit of food to the small bowel.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, none of the patients who underwent BSG in the report by Lemmens et al had %EBWL < 50% at 4 years. Also, Fink et al reported %EBWL of 66.74% and %TBWL of 38.2% after BSG, which were significantly greater than those in the SG patients in their study. Lemmens et al explained in the study that the main effect of the ring or band in SG is satiety more than the physical restriction and slowing of the movement of food, and this mechanism causes continued restriction and triggers the ileal brake mechanism because of the fast transit of food to the small bowel.…”
Section: Discussionmentioning
confidence: 50%
“…reported a significantly greater percentage of EWL in the LBSG group (38.22%) compared with the LSG control (32.69%). Conversely, both LBSG groups had an increased frequency of vomiting . Significant vomiting resulted in MiniMizer ring removal, approximately 8% of patients from both LBSG groups …”
mentioning
confidence: 93%
“…They found no significant difference in weight loss at 12 and 24 months. At 36 months post‐operation, Fink et al . reported a significantly greater percentage of EWL in the LBSG group (38.22%) compared with the LSG control (32.69%).…”
mentioning
confidence: 99%
See 2 more Smart Citations